2014
DOI: 10.1155/2014/132350
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Bioactive Release from Nerve Conduits as a Neurotherapeutic Strategy for Neuronal Growth in Peripheral Nerve Injury

Abstract: Peripheral nerve regeneration strategies employ the use of polymeric engineered nerve conduits encompassed with components of a delivery system. This allows for the controlled and sustained release of neurotrophic growth factors for the enhancement of the innate regenerative capacity of the injured nerves. This review article focuses on the delivery of neurotrophic factors (NTFs) and the importance of the parameters that control release kinetics in the delivery of optimal quantities of NTFs for improved therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 166 publications
(211 reference statements)
0
32
0
2
Order By: Relevance
“…This is consistent with the growing appreciation that application of multiple NTFs, rather than a single type, holds greater therapeutic promise. Noncellular delivery strategies could deliver multiple NTFs, but undesired initial burst release and loss of bioactivity as time progresses hamper the therapeutic effect (8,18,(25)(26)(27)(28). Cellular delivery systems show advantages to providing bioactive NTFs with adequate doses and release kinetics at the site of action and avoiding toxic effects of nonphysiologic protein degradation or aggregation products (28).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the growing appreciation that application of multiple NTFs, rather than a single type, holds greater therapeutic promise. Noncellular delivery strategies could deliver multiple NTFs, but undesired initial burst release and loss of bioactivity as time progresses hamper the therapeutic effect (8,18,(25)(26)(27)(28). Cellular delivery systems show advantages to providing bioactive NTFs with adequate doses and release kinetics at the site of action and avoiding toxic effects of nonphysiologic protein degradation or aggregation products (28).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the release kinetics of NTFs are also an important factor that affects repair outcomes. The burst release of a too-high dose of NGF may hinder axonal growth because of the down-regulation of tropomyosin receptor kinase A and loss of affinity of tropomyosin receptor kinase A to the growth factors (15)(16)(17)(18). Furthermore, many studies have found that a microenvironment with prolonged, high levels of NTFs, which last for several months or even years, is not necessary for nerve regeneration (19,20) and even has an adverse effect on functional recovery and on the elongation of the axon toward the distal target (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, single exogenous dosage of BDNF has shown better results than continuous long-term applications [258]. It is reported that muscle regeneration causes the overexpression of GDNF which increases the number of motor axons in the neuromuscular junctions in vivo [259][260][261][262][263][264][265][266]. Also, GDNF is a potent protective factor against axotomy-induced motor and sensory neuron death [267][268][269][270].…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…Dosing and drug kinetics play an important role in the efficacy of growth factor strategies and excessive delivery can actually impede axonal regeneration 66. A number of biotechnology strategies are being used to develop optimum delivery methods,67 but presently none are approved for use in clinical practice.…”
Section: Surgical Advancesmentioning
confidence: 99%